Prevalence of Musculoskeletal Injuries in Shiraz Male Wushu Players: A Cross Sectional Study - Farahnaz Emami; Masoud Bahremand; Zahra Rojhani-Shirazi (Shiraz University of Medical Sciences, 2017)
Background: Wushu is one of the martial arts that combines explosive strength and speed movements with combat techniques. Most studies to date of wushurelated injuries have been published in Chinese languages. No published studies have reported the prevalence of these injuries in Iran. Therefore, the aim of the present study was to determine the prevalence of musculoskeletal injuries in male wushu players in Shiraz. Methods: Male wushu athletes aged 18 to 30 years were included in this cross sectional study if they had been practicing for 2 hours per session, twice a week during the past 3 years. The athletes were recruited by convenience sampling from 30 wushu clubs in Shiraz, Iran. The sample size was 165. The study was conducted from June to September 2016. Each participant was asked to complete an information questionnaire about his musculoskeletal injuries related to wushu during the previous year. Results: About two third (65.45%) of wushu players had one or more injuries during the previous year. Severe injuries were most commonly located in the head/neck and knee/tibia areas, and inflammation was more prevalent than the other types of injuries. Conclusion: Wushu players in this study reported a high prevalence of injuries affecting different parts of the body.